Baseline use of angiotensin-converting enzyme inhibitor/AT1 blocker and outcomes in hospitalized coronavirus disease 2019 African-American patients. Issue 12 (December 2020) - Shah, Priyank; Owens, Jack; Franklin, James; Jani, Yash; Kumar, Ashish; Doshi, Rajkumar
Abstract : Objectives: The primary objective of this study is to determine the effect of baseline use of angiotensin-converting enzyme inhibitor (ACE-i)/AT1 blocker (ARB) on mortality in hospitalized coronavirus disease 2019 (Covid-19) African-American patients. The secondary objectives are, to determine the effect of baseline use of ACE-i/ARB on the need for mechanical ventilation, new dialysis, ICU care, and on composite of above-mentioned outcomes in the same cohort. Methods: In this retrospective study, we analyzed data using electronic medical records from all hospitalized Covid-19 African-American patients, who either died in the hospital or survived to discharge between 2 March and 22 May 2020. Patients were divided into two groups, those on ACE-i/ARB at baseline and those not on them. We used Pearson chi-square test for categorical variables, and Student's t test for continuous variables. We performed multiple logistic regression to test the primary and secondary objectives using SAS 9.4. Results: Out of 531 patients included in the analysis, 207 (39%) were on ACE-i/ARB at baseline. Patients in ACE-i/ARB group were older (64 vs. 57 years, P < 0.001), and had higher prevalence of hypertension (96.6 vs. 69.4%, P < 0.001) and diabetes mellitus (55.6 vs. 34.9%, P < 0.001). There was no difference in sex, BMI, other comorbidities, and presenting illness severity among the groups. After adjustment of multiple covariates, there was no difference in outcomes between the two groups including mortality, need for mechanical ventilation, new dialysis, ICU care, as well as composite outcomes. Conclusion: Baseline use of ACE-i/ARB does not worsen outcomes in hospitalized Covid-19 African-American patients.